Yield maximization of oriental pickling melon (cucumis melo var.conomon (L) Makino) by high density planting and nutrient management - Rajees P.C (Department of Agronomy, College of Horticulture, 2013)
A field experiment was conducted at the Agricultural Research Station, Mannuthy, Thrissur during December 2011 to February 2012 to study the effect of “Yield maximization of oriental pickling melon (Cucumis melo var. conomon (L.) Makino) by high density planting and nutrient management” grown in summer rice fallows. The objective of the study was to achieve maximum production of oriental pickling melon by high density planting and optimum use of nutrients. The experiment was laid out in Randomised Block Design (RBD) with three replications. Treatments consisted of combinations of five planting densities and three fertilizer levels. The planting densities were 10,000 (S1), 17,777 (S2), 22,222 (S3), 26,666 (S4) and 33,333 (S5) plants per hectare and fertilizer levels at 100% (F1), 125% (F2) and 150% (F3) of recommended dose of fertilizers (RDF) respectively. Plant population, fertilizer levels and their interactions have shown significant effect on growth characteristics. Parameters like number of vines per plant, length of vine at harvest and number of leaves per vine increased with increase in fertilizer dosage but decreased with increase in plant population. LAI and per hectare shoot dry matter production increased with increase in plant population and fertilizer levels. Interactions between plant population and fertilizer levels were linear up to S5F3 on LAI and per hectare shoot dry weight. Yield attributes like number of fruits per plant, mean fruit weight and mean fruit volume declined significantly with increase in plant population. Fruit yield per hectare increased significantly with increase in plant population up to S4 and thereafter decreased significantly. Among the fertilizer levels, all the yield attributes increased significantly up to F2 and slightly decreased at F3. S4F2 recorded significantly the highest fruit yield. There was a steady decline in number of fruits per plant, mean fruit volume and mean fruit weight per plant under each fertilizer level with increase in plant population, but the fruit yield per hectare increased substantially High density planting and levels of NPK had significant effect on leaf Nitrogen, Phosphorus and Potassium contents both at 30 and 60 DAS. The leaf nutrient contents decreased with increase in plant population. Leaf N, P, and K contents increased significantly with increase in fertilizer level up to F3 both at 30 and 60 DAS. There was no significant interaction effect between plant population and levels of nutrients applied. Density of planting and nutrient levels significantly affected shoot nitrogen content at harvest and uptake of N by the crop. The N content of fruit at harvest remained constant at 1.45 per cent irrespective of planting densities. Shoot N content decreased significantly with increase in plant population. N uptake by fruits increased significantly up to S4. The shoot N content increased significantly up to F2 fertilizer level. The interaction between plant population and fertilizer level was significant in the case of total N uptake. Total N uptake by the crop increased significantly under each fertilizer level up to S4 only and then decreased. Similarly in each planting density, significant response to fertilizer level was observed up to F2 only. Therefore S4F2 recorded the highest uptake of N by the crop. Total P and K uptakes also have shown the same trend and highest uptake was observed in S4F2, which recorded the highest fruit yield. High density planting had significant influence on total cost of production, gross returns, net returns and net income per rupee invested. Cost of cultivation was very less in S1, because of wider planting in pits taken at 2 x 1.5 m apart. Cost of cultivation was very high in S3 and S5 due to more number of channels taken at every one metre. Since S2 and S4 were planted in channels taken 1.25 m apart, its cost of cultivation was less compared to S3 and S5. Net return increased with increase in plant population up to S4 and then decreased. Highest net profit per hectare was recorded in S4F2. This is due to the highest fruit yield of 76.9 t/ha recorded in S4F2 and a moderate cost of production compared to other treatment combinations. Hence a population density of 26,666 plants per hectare and a fertilizer dose of 125% RDF were found to be the best treatment for realising highest profit from the cultivation of oriental pickling melon at high density planting using the less spreading variety “Saubhagya”.